Analisis Statistik Asuhan Kesehatan Pasien Rawat Inap Di Rumah Sakit Umum Daerah (RSUD) dr. Rasidin Padang - Dina Oktavia; Ressa Oashttamadea; Yastori Yastori (Iris Journal of Health Information Management, 2022)
Medical records are files that contain records and documents including patient identity, examination results, treatment that has been given, as well as actions and other services that have been provided to patients. Data collection was carried out at the Regional General Hospital Dr. Rasidin Padang by recording data on inpatients who were discharged from the period March 01 - March 31, 2018, so that data were obtained as many as 251 patients with 103 beds. Then data processing was carried out using a computer with the Microsoft Excel application program. Furthermore, the data were analyzed and the results of health care statistical processing were presented in the form of tables and Barber Johnson charts. From the grouping of the most common diagnoses based on ICD-10 at the Regional General Hospital Dr. Rasidin Padang for the period March 01 - March 31, 2018, it was found that the most common code was code A91 as many as 21 patients with a diagnosis of Dengue Haemorrhagic Fever (DHF).Grouping the main diagnoses based on bowel movements in ICD-10 resulted in the highest frequency of diagnoses being BAB I (Certain infectious and paracitic diseases) and BAB XV (Pregnancy, chilbirth and pueperium) as many as 12.75% with a total of 32 patients each. The procedure grouping based on ICD-9 CM in RSUD dr. Rasidin Padang for the period March 01 - March 31, 2018 was SC with procedure code 74.99 as many as 14. Based on the DTD code and its definition, it is known that the most common diagnosis is DTD 032.1 (Dengue hemorrhagic fever) as many as 21 patients. In the RL4a Format table, it is known that the most age group as an inpatient at RSUD dr. Rasidin Padang for the period March 01 - March 31, 2018 is the age group 45 - 64 years as many as 70 patients with female gender as many as 37 patients and male as many as 33 patients, while based on the disposition died as many as 2 and live as many as 249. After data processing, it was obtained that the percentage of BOR at RSUD Dr. Rasidin Padang for the period March 01 - March 31, 2018 had not reached an efficient number because the value obtained was 26.65% or 27%, while the BOR efficiency rate was 60-85%. BTR is 2.44 or 2 times, because the calculation of the BTR number is per year, the BTR efficiency cannot be determined. TI is 9.33 or 9 days. This means that the TI value is not yet at an efficient point, because the TI efficiency value is 1 - 3 days.